Optimization of Polycondensation of Polylactic Acid Using Al(DS)3 Catalyst - Widjaja, Tri; Aziz, Ahmad Musonnifin; Nainggolan, Anggi Tirta Sari Br; Syahbarakat, Rossesari Nailah; Widjadja, Arief (Journal of Fundamentals and Applications of Chemical Engineering, 2024)
Poly(lactic acid) (PLA) is a promising candidate as a renewable resource for plastic production. The use of PLA as a plastic material helps alleviate issues associated with waste. In the production of Polylactic Acid (PLA), by-products such as water are generated, and the Lewis acid catalyst used in PLA production is susceptible to rapid decomposition and deactivation by water. This research aims to optimize PLA polymerization using a water-resistant catalyst, Al(DS)3, to achieve an optimum PLA molecular weight.The synthesized PLA is then analyzed using viscometry to determine its molecular weight. Optimization is carried out using the Response Surface Methodology (RSM) with a Central Composite Design (CCD) matrix. The molecular weight of the synthesized PLA is measured through viscometry, and the data is input into Minitab to obtain the optimum point. This optimum point is further validated by calculating the error value from the optimization results. The optimized PLA results in a molecular weight of 10.313 g/mol with an error value of 4.47% at a catalyst concentration of 0.15% and an operating temperature of 180 °C.